Development of a Cherenkov light imaging system for studying the dynamics of radiocesium in plants. Issue 6 (3rd June 2017) - Kurita, Keisuke; Suzui, Nobuo; Yin, Yong-Gen; Ishii, Satomi; Watabe, Hiroshi; Yamamoto, Seiichi; Kawachi, Naoki
ABSTRACT: High-resolution images of radiocesium ( 137 Cs) distribution are required to study cesium kinetics in plants. A Cherenkov light imaging system can visualize fine distributions of radionuclides emitting beta particles using an optical camera. To evaluate the linearity of the system, an imaging test was performed with point sources of 137 Cs, with a radioactivity of 10–2000 kBq. The results indicated that the system has a good linearity between the image intensity and the radioactivity of 137 Cs. We developed an imaging system for plants using this system to study radiocesium movement in intact plants. To demonstrate the ability to image radiocesium in a plant, an experiment was performed with an intact soybean plant for four days. The root of an 11-day-old soybean plant was dipped in 20 mL of a culture solution containing 137 Cs with a radioactivity of 10 MBq without potassium. After one day, the solution was replaced with one with potassium but no 137 Cs. The soybean plant was in healthy condition in the system, and the high-resolution serial images indicated that 137 Cs was transported to the shoot and accumulated in the node. Therefore, Cherenkov light imaging is promising for imaging radiocesium in intact plants.